2018
DOI: 10.3390/risks6040145
|View full text |Cite
|
Sign up to set email alerts
|

Memory, Risk Aversion, and Nonlife Insurance Consumption: Evidence from Emerging and Developing Markets

Abstract: Policymakers in developing and emerging countries are facing higher risk that is related to natural disasters in comparison to developed ones because of persistent problem of supply-side bottleneck for disaster insurance. Additionally, lower insurance consumption, higher disaster risk, and high income elasticity of insurance demand have worsened the loss consequences of natural disaster in these markets. In this context, current study for the first time argues that the supply side bottleneck problem has its or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 42 publications
(67 reference statements)
0
10
0
Order By: Relevance
“…(2000), Elango and Jones (2011), Esho et al. (2004), Feyen et al (2013), Park and Lemaire (2012), Outreville (1990), Tiwari and Patro (2018), Tiwari et al. (2019) and Trinh et al.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…(2000), Elango and Jones (2011), Esho et al. (2004), Feyen et al (2013), Park and Lemaire (2012), Outreville (1990), Tiwari and Patro (2018), Tiwari et al. (2019) and Trinh et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…, Given this, there has been a growing literature studying the drivers of non‐life insurance expenditure across countries. Typical determinants, as pointed out by earlier studies, include economic factors, such as income and living standards and social factors, such as education, economic freedom and legal framework (Browne et al., 2000; Elango & Jones, 2011; Esho et al., 2004; Lee & Chiu, 2012; Outreville, 1990; Park & Lemaire, 2012; Tiwari & Patro, 2018; Tiwari et al., 2019; Trinh et al., 2016). In reality, however, among countries with a similar level of per capita income, the level of spending on non‐life insurance products varies greatly.…”
Section: Introductionmentioning
confidence: 99%
“…However, the high cost of health insurance remains a significant challenge that limits the effectiveness of these products for the public. Studies have identified market inefficiencies as the main cause of high health insurance costs, which stem from inadequate information exchange [5,2,7,9]. To capture the customer information, the products may be made or updated several times in response to changes in the risk profile of the insured.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, health insurers must ascertain how to deliver both value and quality. To do so, firms have been employing advance ITenabled solutions and employing them at various stages of the insurance value chain [6][7][8]. The level of technology integration is rising every year.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the possibility that parametric insurance might be a more expensive product than traditional insurance is not ignored. The intervention of the public authority by setting up a type of subsidy scheme or a tax deductibility procedure could mitigate this drawback (Tiwari and Patro 2018).…”
Section: The Opportunity To Introduce Parametric Insurance In Romaniamentioning
confidence: 99%